The Impact of E-WOM, Celebrity Endorser, and Brand Image on Purchase Decisions: A Study of MS Glow Cosmetics in Indonesia - Setiawan, Erwin; Rauf, Abdul; Adhimursandi, Doddy (Economics and Business Solutions Journal, 2025)
This study investigates the influence of Electronic Word of Mouth (E-WOM), Celebrity Endorser, and Brand Image on the purchasing decisions of MS Glow cosmetics consumers in Samarinda, Indonesia. While these factors are recognized drivers of consumer behavior, their combined effect in the context of local beauty brands remains underexplored. Data were collected from 120 respondents via a questionnaire and analyzed using Partial Least Squares (PLS). The results demonstrate that all three variables: E-WOM, Celebrity Endorser, and Brand Image have a significant positive influence on purchase decisions. Notably, Brand Image emerged as the strongest predictor. The findings underscore the critical role of a coordinated marketing strategy that leverages credible peer reviews, strategic celebrity partnerships, and consistent brand-building to drive consumer action in the competitive cosmetics market